2020
DOI: 10.1088/1361-6641/ab74f1
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication technique of the Si0.5Ge0.5 Fin for the high mobility channel FinFET device

Abstract: In this paper, a fabrication technique of Si 0.5 Ge 0.5 Fin for the high mobility channel FinFET device is systematically investigated. Although the shallow trench isolation (STI) densification temperature is already reduced from 1050 °C to 850 °C, the Si 0.5 Ge 0.5 Fin with the STI annealing first approach still suffers from thermal instability and micro trench issue. It is no possible to further reduce the STI densification temperature using the traditional furnace annealing for the Si 0.5 Ge 0.5 Fin, becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Therefore by using the same skill, all the parameters in Equations ( 1) and ( 2) are determined to fit the measured characteristic curves except the ones in Figure 2a,b. where the two transistors, denoted by W110L100 (Fin width = 110 nm, Channel length = In addition, all determined k N 's may be specifically listed as in Tables 1-3 at different sizes and at different V G 's [12]. In the modified conventional formula in Equations ( 1) and ( 2), k N is supposed to be inversely proportional to the channel length.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore by using the same skill, all the parameters in Equations ( 1) and ( 2) are determined to fit the measured characteristic curves except the ones in Figure 2a,b. where the two transistors, denoted by W110L100 (Fin width = 110 nm, Channel length = In addition, all determined k N 's may be specifically listed as in Tables 1-3 at different sizes and at different V G 's [12]. In the modified conventional formula in Equations ( 1) and ( 2), k N is supposed to be inversely proportional to the channel length.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the mobility of silicon channel may be promoted by even 2.5 to 4 times as SiGe is technically and sophisticatedly introduced stack by stack. The above advanced techniques and other options are definitely promising and achievable, making FinFET continuously popular as currently [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the introduction of Si 0.5 Ge 0.5 channel was realized by Si 0.5 Ge 0.5 /SiGe SRB fin patterning and low temperature STI process based on STI last scheme. 9 In addition, to further improve the electrical characteristics of the device, a S/D NiPt silicide process and an in situ ozone oxidation followed by HfO 2 /Al 2 O 3 bi-layer high-k dielectric deposition were employed. In particular, to ensure the formation of the low resistivity phase NiSi (Ge) while avoiding excessive solidification in silicide process, 13 the unreacted NiPt was selectively removed with HNO 3 : HCI (1:3) after the first rapid thermal annealing (RTP) treatment of 310 °C for 60 s. Then, a second RTP treatment of 500 °C for 10 s was performed to induce the change of the remaining Ni 2 Si (Ge) convert to the desired NiSi(Ge).…”
Section: Methodsmentioning
confidence: 99%
“…7 In our previous work, we investigated the epitaxial growth of strain relaxed buffer (SRB) layer and Si 0.5 Ge 0.5 channel introduction technique based on STI last scheme. 8,9 However, it is necessary to further overcome some other challenges, such as leakage of parasitic sub-fin channel, interface state density (Dit) of SiGe channel, and large source-drain series resistance of fin structure. [10][11][12] Therefore, for Si 0.5 Ge 0.5 channel FinFET, the fabrication of the device and its electrical characteristics optimization need to be further investigated, as relatively few studies have been reported so far.…”
mentioning
confidence: 99%
“…The low-Ge-content SiGe channel will be implemented firstly on the FinFET owing to its advantages of higher hole mobility, better negative bias temperature instability (NBTI) reliability than silicon and more compatible with present silicon platform [ 4 , 5 ]. So far, a SiGe channel can be integrated in FinFET architectures in multiple ways, e.g., by shallow trench isolation (STI) last scheme [ 6 ] or by STI first strategy [ 7 ] or epitaxial cladding of Si Fins [ 8 ]. However, a high quality of low-Ge-content SiGe epitaxial grown on Si substrate is still a challenge task to solve the epitaxial thickness limit of SiGe film and the threading dislocations (TD) defects.…”
Section: Introductionmentioning
confidence: 99%